Inferior Vena Cava Filter Retrieval Trends: A Single-Center Experience - Ionescu, Filip; Anusim, Nwabundo; Ma, Eva; Qu, Lihua; Blankenship, LeAnn M.; Stender, Michael; Jaiyesimi, Ishmael (TH Open, 2021)
Recognition of the adverse events of inferior vena cava filters (VCFs) has prompted the Food and Drug Administration (FDA) to issue safety warnings (2010 and 2014), advocating for removal, once the risk of pulmonary embolism has abated. Despite an initial increase in retrieval rates, these remain low (25–30% at 1 year in 2014). We retrospectively investigated retrieval trends in adults with VCFs placed between 2015 and 2018 at a single institution. The rate of retrievable VCF removal accounting for the competing risk of death was the main outcome. There were 494 VCFs placed (305 retrievable). The cumulative incidence of retrieval remained low (21% at 1 year), even after the second FDA warning (2014). Patients who resumed anticoagulation (AC) at any time were more likely to have retrieval (hazard ratio [HR] = 3.6, p < 0.01) and had higher retrieval rates at every time point (31.4 vs. 7.6% at 1 year). Advanced age (HR = 0.98 per year, p = 0.004), stroke (HR = 0.28, p = 0.028), and active malignancy (HR = 0.42, p = 0.006) predicted nonretrieval. Device-related complications were infrequent (<1%) but thrombotic complications occurred early and were more common for nonretrieved VCFs (17 vs. 12%, p = 0.29). Revision of guidelines to recommend active surveillance for the ability to tolerate AC in the immediate postimplantation period may improve retrieval rates.
Keywords: IVC filter; retrieval; thrombosis; filter failure; practice trends